Optimization of empty palm fruit bunch pyrolysis over HZSM-5 catalyst for production of bio-oil - Saidina Amin, Nor Aishah; Asmadi, M. (2008)
The concerns over depletion of fossil fuel and security of energy supply have directed increasing awareness about biomass derived energy. Empty palm fruit bunch (EPFB), one of the major biomass available in Malaysia, is a potential source for fuel production. The objective of the present work is to determine the effect of reaction temperature and time on the optimization of EPFB pyrolysis to produce renewable bio-oil. A 2(2) central composite rotatable design (CCRD) was adopted in designing of experiments and response surface methodology was implemented. Experimental results were thoroughly analyzed by Analysis of Variance (ANOVA). The optimum product yield of 40.48 % was achieved at 573.15 K in 15 min while 0.057(g/g) of product selectivity was obtained at 623.15 K in 20 min.